PERBEDAAN ASUPAN MAKRONUTRIEN MAHASISWA ASING SEBELUM DAN SAAT TINGGAL DI SURABAYA, INDONESIA - Levina, Airin; Muniroh, Lailatul (GIZI INDONESIA, 2018)
Population transfers between countries occur a lot, especially because of education. There are many international students in various parts of the world, including in Surabaya, Indonesia. Environmental differencescause changesin the eating habits that affect the amount of macronutrients intake among international students. The aims of this research was to analyze the differences of macronutrients intake among international students before and while live in Surabaya. This study was a cross-sectional design with 30 samples. Data were collected by in-depth interviews, the Dietary History instruments and Semi Quantitative Food Frequency Questionnaire through interview. Data were  analized  by t-test through the SPPS application. The results showed that there were differencesin macronutrient intake of international students before and during their stay in Surabaya (p<0,005). There  was a decrease in the average intake of energy, proteins, fat, and carbohydrates. It was due to inadequate access to food, often skipping meals, and can not accept the taste of Indonesian cuisine. Frequency and number of food portions of international students need to be increased.In addition, assistance from the universities are needed to increase access to food for international students.  ABSTRAK  Perpindahan penduduk antar negara banyak terjadi, khususnya karena pendidikan. Terdapat banyak pelajar internasional di berbagai belahan dunia, termasuk di Surabaya, Indonesia. Perbedaan lingkungan menyebabkan perubahan kebiasaan makan mahasiswa asing yang mempengaruhi jumlah asupan makronutriennya. Tujuan dari penelitian ini adalah menganalisis perbedaan asupan makronutrien pada mahasiswa asing sebelum dan saat tinggal di Surabaya. Penelitian ini adalah penelitian cross-sectional dengan 30 sampel. Data dikumpulkan dengan wawancara mendalam, instrument Dietary History dan Semi Quantitative Food Frequency Questionnaire melalui wawancara. Analisis data menggunakan uji t melalui aplikasi SPSS. Hasil penelitian menunjukkan ada perbedaan asupan makronutrien mahasiswa asing pada sebelum dan saat tinggal di Surabaya (p<0,005). Terjadi penurunan rata-rata asupan energi, protein, lemak, dan karbohidrat. Hal tersebut disebabkan oleh akses makanan yang tidak memadai, seringnya melewatkan waktu makan, dan mahasiswa asing belum sepenuhnya dapat menerima rasa masakan Indonesia. Frekuensi dan jumlah porsi makanan mahasiswa asing perlu ditingkatkan. Selain itu, perlu bantuan dari pihak universitas masing-masing untuk meningkatkan akses makanan mahasiswa asing. Kata kunci: asupan, makronutrien, mahasiswa asing